(untitled) (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2021)
PT. Asuransi Simas Insurtech makes a taxation application to assist companies in carrying out taxation documentation both corporate tax documents and for counterparties. This application was created as a means to simplify and shorten the workings of companies and transaction opponents to access their tax documents or data. This study aims to determine whether the taxation application system of PT. Insurance Simas Insurtech can be accepted or not by employees and transaction opponents of PT. Insurance Simas Insurtech. From known problems, measurements are made using the right method. PT. Asuransi Simas Insurtech as the object of research. The tool for conducting this research is to use the Technology Acceptance Model method in the taxation application system at PT. Insurance Simas Insurtech. The relationship between the four factors that influence the acceptance of the taxation application system, namely, the perception of ease, perceived usefulness, user attitude and user interest in receiving the taxation application system. Users really believe that the system is indeed very beneficial and there is ease of use. This factor triggers an increase in the value of the taxation application of PT. Insurance Simas Insurtech for users.